Influence of Layer Thickness on the Drying of Lithium‐Ion Battery Electrodes—Simulation and Experimental Validation. Issue 5 (29th March 2021) - Kumberg, Jana; Baunach, Michael; Eser, Jochen C.; Altvater, Andreas; Scharfer, Philip; Schabel, Wilhelm
Abstract : In this work, a detailed study of the drying of battery electrodes of different thicknesses is presented. A mathematical model to calculate the solvent loading and film temperature over the drying time is experimentally validated. The model is based on a first study presenting a simulation model to predict the drying course when linear drying kinetics prevail and no resistance exists for solvent transport within the film. To shed some light on the drying behavior of electrode films with different thicknesses, the start of capillary pore emptying is observed using a digital microscope. In the experiments, an onset of capillary transport even before the end of film shrinkage is observed for the electrode films with thicknesses above state‐of‐the‐art‐thickness. A clusterwise drying behavior becomes more distinct for thicker electrodes, with large areas of dry and wet capillaries next to each other, compared to a more homogenous drying of the thin electrodes. Based on these findings, the linear model is extended to consider transport limitations within the porous electrode film in the form of a moving drying front. The experiments show an increasing deviation from the linear model with increasing electrode thickness and the extended simulation, which considers transport resistances within the film, shows good agreement. Abstract : In this study, experimental drying curves of electrodes of different film thicknesses are compared with a simulation that takes the transport limitations that occur during the drying of thicker electrodes into account. The simulation shows good agreement with the experiment. The onset of capillary drying, which is an important time in the drying of thicker electrodes, is experimentally illuminated.